Career Path Education in Preparing Students Entering The Workforce - Indo Sennang; Handy Wiranto; Desti Purnamasari (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2026)
Student career readiness is one of the factors that contribute to the high level of educated unemployment, including in psychology students who have a variety of career path options but lack of directed planning. This activity aims to increase the understanding and career readiness of psychology students through structured career path education. The method used is a quantitative approach with a pre-test and post-test one group    design through career path education training for 74 S1 students of the Psychology Study Program, University of Muhammadiyah East Kalimantan. Activities were carried out through lectures, audio-visual media, interactive discussions, and reflections, with evaluations using measurements of career readiness and understanding before and after training. The results of the evaluation showed an increase in students' understanding and career readiness, an average increase of 11.5 points after treatment/intervention, characterized by clarity of career direction and reduced confusion in determining career choices. Career path education is effective as a strategy to strengthen the readiness of psychology students in facing the world of work.Kesiapan karier mahasiswa merupakan salah satu faktor yang berkontribusi terhadap tingginya tingkat pengangguran terdidik, termasuk pada mahasiswa psikologi yang memiliki beragam pilihan jalur karier namun masih kurang dalam perencanaan yang terarah. Kegiatan ini bertujuan untuk meningkatkan pemahaman dan kesiapan karier mahasiswa psikologi melalui pendidikan jalur karier yang terstruktur. Metode yang digunakan adalah pendekatan kuantitatif dengan desain one group pre-test dan post-test melalui pelatihan pendidikan jalur karier pada 74 mahasiswa S1 Program Studi Psikologi Universitas Muhammadiyah Kalimantan Timur. Kegiatan dilaksanakan melalui ceramah, media audio-visual, diskusi interaktif, dan refleksi, dengan evaluasi menggunakan pengukuran kesiapan dan pemahaman karier sebelum dan sesudah pelatihan. Hasil evaluasi menunjukkan adanya peningkatan pemahaman dan kesiapan karier mahasiswa, dengan rata-rata peningkatan sebesar 11,5 poin setelah perlakuan/intervensi, yang ditandai dengan kejelasan arah karier dan berkurangnya kebingungan dalam menentukan pilihan karier. Pendidikan jalur karier terbukti efektif sebagai strategi untuk memperkuat kesiapan mahasiswa psikologi dalam menghadapi dunia kerja.